Економічний нігілізм лідерів Української революції 1917–1921 рр. як детермінант поразки за українську державність на початку ХХ ст. - Чуткий, Андрій Іванович (Київський національний університет імені Тараса Шевченка, 2021)
Економічний чинник, як важливий детермінант поразки Української революції 1917–1921 рр., ще й досі неналежно досліджений. Водночас сам характер розвитку людства з моменту переходу до капіталізму вивів економічну сферу на ключову позицію в житті кожної людини. Ця тенденція особливо посилилась на початку XX ст. Це засвідчили дві світові війни та інші військово-політичні конфлікти, постійно зростаюче прискорення в характері економічного розвитку та формування суспільства масового споживання, що само по собі посилювало залежність кожного індивіда від економічної сфери. Враховуючи таке значення економіки для життя модерного суспільства доцільно з'ясувати як поставились до неї провідники українського державотворення початку XX ст. Унаслідок дослідження отримано комплекс фактичних даних, що чітко засвідчують – економічний чинник був важливим у поразці Української революції 1917–1921 рр., оскільки українські державні мужі того часу не зрозуміли важливості економічної сфери життя. Окремо слід виділити надмірний ідеалізм і водночас повальне захоплення соціалістичною доктриною, що в своїй основі суперечило нормальному будівництву економіки.

The economic factor, as an important determinant of defeat of the Ukrainian Revolution of 1917–1921 is still insufficiently studied. At the same time, the very nature of human development since the transition to capitalism has led the economic sphere to a key position in the life of every person. This trend has intensified since the early 20th century. This was evidenced by two world wars and other military-political conflicts, constantly increasing acceleration in the nature of economic development and the formation of a society of mass consumption, which in itself increased the dependence on the economic sphere of each individual. So, this is an axiom. Given the importance of the economy for the life of modern society, it is advisable to find out how the leaders of Ukrainian statehood reacted to it on the beginning of the 20th century. Moreover, there are still not enough studies of this kind. As a result of the study, a complex of actual data is obtained, which shows – economic factor was important in the defeat of the Ukrainian Revolution of 1917–1921, because Ukrainian statesmen at that time did not understand the importance of the economic sphere of life. The data that proves it can be conditionally divided into two groups. The first one – are the initial negative factors, which were not caused by the activities of Ukrainian political leaders, but were laid down by a long period of previous colonial development of Ukraine. However, these leaders did not take any steps to overcome that negative influence. These included: the absence of a significant number of truly wealthy people among the leaders of Ukrainian statehood, and therefore antagonism about the wealthy people between those leaders, which eventually deprived the Ukrainian statehood of internal material resources; disbelief in the possibility of independent development of Ukraine and stubborn clinging to autonomous ties with Russia; anarchism of the masses (especially the peasantry), generated by the years of war and especially by the brutal policies of the previous imperial government, which was reinforced by the activities of the Bolsheviks; shortage of patriotic specialists; the revived Ukrainian statehood lived in war conditions throughout the period of its existence, which made normal economic development impossible; the main region where the Ukrainian government lasted longer was the agrarian Right-Bank, while the industrial east was always quickly captured by enemy and the Ukrainian government had almost no influence on cities, where industry was concentrated and without its potential the existence of state is simply impossible. The second group of factors that affected negatively on the cause of the Ukrainian statehood in the beginning of the 20th century – are the practical actions of the then Ukrainian political leaders in the economic sphere. These included: the indefiniteness of the higher authorities competence and the uncertainty of their legal status; slow establishment of Ukrainian organs of power, who were responsible for economic issues; there was no clear vertical of accountable local authorities, and consequently the lack of understanding of the situation outside Kyiv; legislative framework, created in the economic sphere, was limited mainly to declarations and was not completed; Ukrainian political leaders did not have a single vision of solving a key issue for Ukraine's economy – agriculture; inefficiency in addressing other economic issues (adjustment of industry, transport, trade, food supplies, taxation and money circulation). Separately should be highlighted the excessive idealism and, at the same time, a widespread fascination with socialistic doctrine, which at its core contradicted the normal construction of the economy. Establishment of these "thin spots" in the economic policy of the Ukrainian government in the beginning of the 20th century is important for today, because a number of mistakes of that time are presented in the policy of the modern Ukrainian government. Accordingly, the bitter experience of the past (loss of statehood due to neglect / procrastination of important economic issues) should play the role of the most powerful argument in the need for rapid change of the situation in economic construction right now.
Economic nihilism of the leaders of the Ukrainian revolution of 1917–1921 as a determinant of defeat for ukrainian statehood in the beginning of the 20th century
Keywords: економічна політика держави; економічна історія України; Українська революція 1917–1921 рр.; українське державотворення ХХ ст.; Українська Центральна Рада; economic policy of the state; economic history of Ukraine; the Ukrainian revolution of 1917–1921; Ukrainian state formation of the 20th century; Central Council of Ukraine